2006
DOI: 10.1016/j.cell.2006.09.032
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Hit Trigger for siRNA Biogenesis in Plants

Abstract: In Arabidopsis, microRNA-directed cleavage can define one end of RNAs that then generate phased siRNAs. However, most miRNA-targeted RNAs do not spawn siRNAs, suggesting the existence of additional determinants within those that do. We find that in moss, phased siRNAs arise from regions flanked by dual miR390 cleavage sites. AtTAS3, an siRNA locus important for development and conserved among higher plants, also has dual miR390 complementary sites. Both sites bind miR390 in vitro and are functionally required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
707
2
15

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(748 citation statements)
references
References 35 publications
24
707
2
15
Order By: Relevance
“…The TAS3a-c transcripts (pri-TAS3a-c) that require two miR390 target sites for tasiRNA production have some short ORFs, but no . 30-nt ORFs that encompass either miR390 target site are found (Axtell et al, 2006;Howell et al, 2007;Montgomery et al, 2008a). The fact that tasiRNAs are produced even without ORFs that encompass miRNA recognition sites is consistent with our results of mutational analysis for TAS2 ORF3 and indicates that these ORFs are not absolutely required but facilitate tasiRNA production.…”
Section: Sde5 Acts On the Tas2 Cleavage Fragments Before Dsrna Synthesupporting
confidence: 79%
See 1 more Smart Citation
“…The TAS3a-c transcripts (pri-TAS3a-c) that require two miR390 target sites for tasiRNA production have some short ORFs, but no . 30-nt ORFs that encompass either miR390 target site are found (Axtell et al, 2006;Howell et al, 2007;Montgomery et al, 2008a). The fact that tasiRNAs are produced even without ORFs that encompass miRNA recognition sites is consistent with our results of mutational analysis for TAS2 ORF3 and indicates that these ORFs are not absolutely required but facilitate tasiRNA production.…”
Section: Sde5 Acts On the Tas2 Cleavage Fragments Before Dsrna Synthesupporting
confidence: 79%
“…These modifications allow the export of transcripts from the nucleus to the cytoplasm where pri-TASs are cleaved by AGO1-RISCs containing 22-nucleotide (nt) miRNAs (e.g. microRNA173 [miR173] in Arabidopsis [Arabidopsis thaliana]) or AGO7-RISCs containing microRNA390 (miR390; Axtell et al, 2006;Chen et al, 2010;Cuperus et al, 2010;Felippes and Weigel, 2009;Montgomery et al, 2008aMontgomery et al, , 2008b. The cleavage results in poly(A)-deficient 59 fragments and uncapped 39 fragments, which are associated with the RISC and SUPPRESSOR OF GENE SILENCING3 (SGS3) and protected from degradation (Yoshikawa et al, 2005.…”
mentioning
confidence: 99%
“…The phasiRNAs, including one tasiARF, are produced downstream of both cleavage sites. The demonstrated cleavage at both 39 and 59 sites of fve-TAS3S by the PARE data argues against an absolute requirement for a noncleavable 59 site in the two-hit mode of tasiARF biogenesis (Axtell et al, 2006;Allen and Howell, 2010). miR828 is conserved in eudicots (Cuperus et al, 2011); although it was not identified in our list of known or conserved miRNAs due to its extremely low expression level, its cleavage of fve-TAS4 and tasiRNA production were confirmed by the PARE data and phasing analyses, respectively (Fig.…”
Section: Conserved Tasirna Pathways In F Vescamentioning
confidence: 62%
“…It could also be, as indicated in a very recent report, that a "normal" RNA with two sRNA target sites could also become a source of secondary sRNAs and, consequently, a node (Axtell et al 2006). RNAs with aberrancy at both ends might also generate sRNAs in the absence of target- Figure 4.…”
Section: Cascades and Networkmentioning
confidence: 99%